2017
DOI: 10.4103/0019-5413.201703
|View full text |Cite
|
Sign up to set email alerts
|

Transforaminal lumbar interbody fusion versus instrumented posterolateral fusion in Grade I/II spondylolisthesis

Abstract: Background:Spondylolisthesis refers to slippage of one vertebra over the other, which may be caused by a variety of reasons such as degenerative, trauma, and isthmic. Surgical management forms the mainstay of treatment to prevent further slip and worsening. However, there is no consensus regarding the best surgical option to treat these patients. This study compares TLIF and instrumented PLF in patients with Grade I and II spondylolisthesis and analysis the outcome with respect to functional outcome, pain, fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Various other studies have found no significant differences in complications and readmission rates between TLIF and PLF in heterogeneous populations of patients, 31 including a cohort of patients with grade 1 to 2 degenerative spondylolisthesis. 32 In 109 patients with spondylolisthesis, Glassman et al 33 found no difference in discharge disposition between the two approaches. Similarly, previous studies have found comparable RTW rates between TLIF and PLF.…”
Section: Discussionmentioning
confidence: 99%
“…Various other studies have found no significant differences in complications and readmission rates between TLIF and PLF in heterogeneous populations of patients, 31 including a cohort of patients with grade 1 to 2 degenerative spondylolisthesis. 32 In 109 patients with spondylolisthesis, Glassman et al 33 found no difference in discharge disposition between the two approaches. Similarly, previous studies have found comparable RTW rates between TLIF and PLF.…”
Section: Discussionmentioning
confidence: 99%
“…The authors argued that a better radiologic union does not necessarily translate into a better clinical outcome when treating spondylolisthesis surgically. Similarly, Pooswamy et al [20] in a retrospective analysis, 40 patients with low-grade spondylolisthesis who had been monitored for 3 years were compared for surgical results between TLIF and instrumented PLF. Except for more operating time in the TLIF group, they discovered identical clinical and radiologic outcomes in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the health-related outcomes are not significantly different between the two procedures [ 18 ]. Pooswamy et al conclude that TLIF and instrumented PLF are equally efficacious options in the treatment of Grade I and II spondylolisthesis, except lytic type [ 19 ].…”
Section: Discussionmentioning
confidence: 99%